(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
The study was conducted with the aim of utilizing leaf meal prepared from Leucaena leucocephala and Gliricidia sepium trees from silvipasture model of agroforestry as alternate feeding strategy on partial replacement of feed ingredients in compound feeds of goat kids and buffalo calves. The edible leaf biomass from Leucaena leucocephala and Gliricidia sepium was 9.20 and 18.54 MT/ha/year respectively and their respective crude protein content was 14.81 and 17.66 per cent. Two feeding trials were conducted with Leucaena leucocephala and Gliricidia sepium leaf meal mix (1:1 ratio) incorporated in concentrate feed for goat kids and buffalo calves at 30 per cent inclusion. The average daily gain of goat kids and buffalo calves fed tree leaf meal incorporated concentrate feed was comparable to daily gain of kids / calves fed conventional concentrate feed in 90 days feeding trial. It was concluded that tree leaf meal (Leuceana leucocephala / Gliricidia sepium - 1:1) can be included up to 30% level in concentrate feed of goat kids and buffalo calves without any change in the growth rate but reducing feed cost.